The impact of antibiotic use on dental enamel development defects: a systematic review of studies in animal models - Alana Cândido Paulo,; Kelly Fernanda Molena,; Bruna Maria Moreira,; Fabrício Kitazono de Carvalho,; Raquel Assed Bezerra Segato,; Francisco Wanderley Garcia de Paula e Silva, (Revista Sul-Brasileira de Odontologia, 2025)
Dental enamel development defects (DDEs) affect up to 40% of individuals and result from genetic, epigenetic, systemic, or local factors. DDEs are classified as hypomineralizations (qualitative defects) or hypoplasias (quantitative defects). Prolonged antibiotic use, particularly amoxicillin in early childhood, has been suggested as a potential cause. While in vitro studies indicate an effect on amelogenesis, no systematic reviews have analyzed this association in animal models. This study systematically reviews animal studies on amoxicillin’s impact on DDEs. Objective: To systematically review animal studies investigating amoxicillin’s effects on dental enamel defects. Material and methods: This review follows PRISMA guidelines. The PICOS strategy defined eligibility criteria, focusing on animal studies assessing amoxicillin’s effects on enamel. Exclusion criteria included: (1) non-animal models, (2) other drug therapies, (3) antibiotics other than amoxicillin, (4) literature reviews or editorials, and (5) in vitro studies. A comprehensive search in PubMed, Embase, and Web of Science was conducted without restrictions. Two independent reviewers screened titles/abstracts, resolving conflicts through a third reviewer. Data extraction included study details (author, year, animal model, dose, and enamel evaluation method). Bias risk was assessed using SYRCLE criteria. Results: From 141 articles, 84 duplicates were removed. After screening, 9 studies (2011–2020) remained for full-text analysis, including 8 case-control studies and 1 randomized clinical trial. Animal models included pigs, mice, and rats, with amoxicillin doses ranging from 50 mg/kg to 3.0 g/kg. Enamel defects were assessed via X-ray microtomography, scanning electron microscopy, and histological staining. Some studies reported reduced enamel mineral density and structural changes in ameloblasts, while others found no significant effects. Conclusion: Animal studies suggest a potential link between amoxicillin use and DDEs, particularly enamel hypomineralization. However, inconsistencies in study designs, doses, and evaluation methods highlight the need for further research.